Alterations of C-MYC, NKX3.1, and E-cadherin expression in canine prostate carcinogenesis - Fonseca-Alves, Carlos Eduardo [UNESP]; Rodrigues, Marcela Marcondes Pinto [UNESP]; Moura, Veridiana Maria Brianezi Dignani de; Rogatto, Silvia Regina [UNESP]; Laufer-Amorim, Renee [UNESP] (Wiley, 2013)
The dog (canis lupus familiaris) is the only other species besides humans thatdevelop spontaneous prostatic carcinomas (PCa) at a high frequency. The canine model is pri-marily utili zed for the study of the PCa molecular mechanisms and provides a natural animalmodel for the study of potential therapies. In humans, the PCa frequently exhibits mutations inthe C-MYC and a reduced expression of the E-cadherin and NKX3.1 proteins. This study’s objec-tivewastoevaluatetheNKX3.1,C-MYC,andE-cadherinexpressioninthecaninenormalpros-tate, benign p rostatic hyperplasia (BPH), proliferative inflammatory atrophy (PIA) and PCa andto verify differences in expression and subcellula r localiz ation of these proteins in the prostaticcarcinogenesis. A tissue microarray (TMA) slide was constructed, and immunohistochemistrywith antibodies raised against C-MYC, NKX3.1, E-cadherin and p63 was performed using theperoxidase and DAB methods. The C -MYC protein expression was elevated in the cytoplasm andnuclei of t he canine PCa a nd PIA compared with the normal prostate (P 5 0.004. The NKX3.1protein expression was reduced in 94.75% o f the PCa and 100% of the PIA compared with thenormal prostate (P 5 0.0022). In fact, t he expression of E-c adherin trended towards a decrease incarcinomas when compared t o normal p rostate and PIA. By immunohistochemistry, more p63-positive basal cells were observed in the P Ca and PIA when compared with the normal prostate(P 5 0.0002). T his study has demonst rated that the carcinogenesis of canine prostatic tissue maybe related to basal cel l proliferation, the gain of C-MYC fu nc tion and the loss of NKX3.1 pr oteinexpression.
Keywords: Canine; Prostatic carcinoma; Immunohistochemistry; Protein expression